2014
DOI: 10.1158/1541-7786.mcr-14-0004
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 Translocations in Bladder Cancer: Differential Sensitivity to HSP90 Inhibition Based on Drug Metabolism

Abstract: Activating mutations and/or overexpression of FGFR3 are common in bladder cancer, making FGFR3 an attractive therapeutic target in this disease. In addition, FGFR3 gene rearrangements have recently been described that define a unique subset of bladder tumors. Here, a selective HSP90 inhibitor, ganetespib, induced loss of FGFR3-TACC3 fusion protein expression and depletion of multiple oncogenic signaling proteins in RT112 bladder cells, resulting in potent cytotoxicity comparable with the pan-FGFR tyrosine kina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 41 publications
(61 reference statements)
3
51
0
Order By: Relevance
“…The existence of FGFR3-TACC3 fusions in human cancers creates additional challenges and opportunities for identifying effective treatment strategies. For instance, a recent study showed that the HSP90 inhibitor ganetespib exerted pleiotropic effects on mitogenic and survival pathways in cells expressing oncogenic gene rearrangements of FGFR3, and provided an alternative therapeutic approach in addition to the pan-FGFR tyrosine kinase inhibitor BGJ398 (47). Further study of novel pathways activated by the FGFR3-TACC3 fusion protein, and a deeper understanding of the molecular details exploited by FGFR3-TACC3 to achieve its biologic potency, can be expected lead to novel therapeutic paradigms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of FGFR3-TACC3 fusions in human cancers creates additional challenges and opportunities for identifying effective treatment strategies. For instance, a recent study showed that the HSP90 inhibitor ganetespib exerted pleiotropic effects on mitogenic and survival pathways in cells expressing oncogenic gene rearrangements of FGFR3, and provided an alternative therapeutic approach in addition to the pan-FGFR tyrosine kinase inhibitor BGJ398 (47). Further study of novel pathways activated by the FGFR3-TACC3 fusion protein, and a deeper understanding of the molecular details exploited by FGFR3-TACC3 to achieve its biologic potency, can be expected lead to novel therapeutic paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Received December 22, 2015; revised January 12, 2016; accepted February 3, 2016; published OnlineFirst February 11, 2016. …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…insensitive to resorcinol-based HSP90 inhibitors due to endogenous glucoronidation (27). STA-12-8666 treatment significantly suppressed SW780 tumor growth (Fig.…”
Section: Hdc Exposure Is Therapeutically Superior To Combination Irinmentioning
confidence: 93%
“…Activation and dimerization of FGFR3 result in cell proliferation or differentiation via signal transduction pathways (10). Point mutations in transmembrane domain of FGFR3 have been identified as a causative factor for skeletal development disorders such as achondroplasia and hypochondroplasia (7,30).…”
Section: Discussionmentioning
confidence: 99%
“…Two membrane-proximal D2 and D3 domains, and interconnecting D2-D3 linker bear the determinants of ligand binding and specificity (10). The Ig-domain III is encoded by two separate exons, exon 8 and exon 9.…”
Section: Introductionmentioning
confidence: 99%